Produção de hidrogênio a partir de água residuária de indústria de fécula de mandioca. - Andreani, Cristiane Lurdes (2012)
Attempting to associate waste treatment to the production of clean and renewable energy, the present research aimed to evaluate the biological production of hydrogen using wastewater from the manioc starch treatment industry, a liquid wastewater of high organic content, generated during the processes of extraction and purification of manioc starch. The experiment was carried out in two upflow fixed-bed anaerobic reactors. As support, bamboo stems and low density polyethylene scraps. Made with pexiglass, each reactor was built with 75 cm of height, with 2.96 L of useful volume for the reactor with bamboo support and 3.13 L for the one with Polyethylene support. The inoculum, collected in a pilot anaerobic reactor, received thermal pretreatment and was recirculated in the reactors for 48 h. Then, alimentation was initiated in a continuum manner. The system was operated with hydraulic detention time (TDH) of 4 and 3 h, at 36 °C and initial pH of 6.0. In the TDH of 4 h, 3 organic loading rates were applied (COV), of 28; 15 and 26 g.L-1.d-1; in the TDH of 3 h 4 COV were applied, of 35; 22; 22 and 27 g.L-1.d-1. The application of the COV did not follow any particular pattern due to the variability of the wastewater constitution. Hence, the effects of TDH, COV and the support mean on the production of hydrogen were evaluated, as well as the influence of bamboo and of low density polyethylene in the fixation and selection of microorganisms that produce hydrogen. Maximum hydrogen production in the reactor using bamboo was of 2.9 L.d-1 in TDH 4h and of 2.2 L.d-1 in the reactor using polyethylene in TDH of 3 h. Hydrogen percentage of 25% in biogas was reached in the reactor using bamboo and of 29% in the reactor using polyethylene. The yielding obtained was of 0.6 L H2.g-1sugar in the reactor using bamboo in TDH 4 h and of 0.8 L H2.g-1sugar in the reactor using polyethylene in TDH 3 h. In both reactors, the mean total sugar removal was of approximately 90%.